Penilaian Kerentanan Pesisir Berdasarkan Parameter Fisik di Pantai Utara Kabupaten Bekasi - Handiani, Dian Noor; Heriati, Aida; Herlambang, Hafidz M. Ashary; Wardhani, Eka (Pusat Riset Kelautan, 2024)
Northern part of Bekasi Regency (Pantura Bekasi) has diverse land: a port area, fisheries, marine tourism, agriculture, residential, industrial and government. Various types of development are occured to support the community welfare. Developments occur without considering sustainability will result in a decline of environmental conditions, and each region will have its own ability to anticipate the impacts of changes that occurs. This research studied coastal vulnerability in the Pantura Bekasi and the relationship between their coastal physical parameters and the vulnerability. Field observations were also conducted as field validation and perceive current conditions. The results show that vulnerability is very high in Fishery port (PPI) Muara Jaya port zone (Mekar Coast), and low vulnerability occurred in Taruma Jaya port zone (Taruma Jaya Coast). Two paramaters are different in these two locations, they are coastline change and geomorphological. The coastline change at Mekar Coast is abrasion, and Taruma Jaya Coast is accretion. The geomorphological at Mekar Coast are a muddy beach and delta, while Taruma Jaya Coast is a swampy beach. Field conditions show that Mekar Coast has low mangrove density, while Taruma Jaya Coast has high mangrove density. These results hopefully can be used as policy consideration for the local government in optimizing coastal management planning, where the spatial plan for Pantai Mekar Beach is designated as a conservation area and demersal fisheries, while on Pantai Taruma Jaya as a public use area such as for Gas and Steam Power Plant (PLTGU) Muara Tawar, PPI Paljaya and port zone.